Media Kompos Serbuk Gergaji Kayu Sengon dan Pupuk Lepas Lambat untuk Meningkatkan Pertumbuhan Semai Pinus merkusii di KPH Banyumas Timur - Suryo Hardiwinoto; Nur Adin Eko Saputro; Handojo Hadi Nurjanto; Widiyatno Widiyatno (Jurnal Ilmu Kehutanan, 2010)
Effects of Composted Sawdust of Falcata Media and Slow Release Fertilizer to Promote  Pinus merkusii Seedling growth in Banyumas Timur FMUPhysical and chemical properties of the potting media, especially porosity and nutrient availability, are required to produce good quality seedlings of pine (Pinus merkusii Jungh et de Vries). Composted sawdust of sengon (Paraserianthes falcataria) wood is a potential material to be used for growing media of pine seedlings. However, since this material contains low nutrients, addition of a slow release fertilizer is required to meet the nutrient demand of seedling growth. The objective of this research was to determine the effects of wood sawdust compost and slow release fertilizer on the growth of pine seedlings. The experiment was arranged in a completely randomized design with two factors and four replications. The first factor was the rate of sawdust compost and the second factor was the rate of slow release fertilizer. Height and root-collar diameter were measured at 6 months of age. As the results, sawdust compost and slow release fertilizer gave a significant effect on height and diameter growths. However, the effect of sawdust compost on seedling growth depended on the rate of fertilizer. Combination treatment that gave the best seedlings growth was 100% sawdust compost + 0% soil (and 12 g fertilizer /1.5 liter media). The seedlings applied with this treatment had the mean height of 8.72 cm and diameter of 2.24 mm, which were significantly greater than the control with the mean height and mean diameter of 1.87 cm and 1.15 mm respectively.